Efficient emissive fluorene-based p–n conjugated porous materials for near-white electroluminescence: benefits of metal-free Friedel–Crafts green polymerization. Issue 44 (21st September 2018) - Wei, Chuan-Xin; Bai, Lu-Bing; An, Xiang; Han, Ya-Min; Liu, Yu-Qin; Yu, Meng-Na; Lin, Jin-Yi; Lin, Zong-Qiong; Xie, Ling-Hai; Xu, Man; Zheng, Qing-Huang; Zhao, Jian-Feng; et al.
Abstract : Efficient emissive fluorene-based p–n conjugated porous materials (CPMs) have been constructed via an effective Friedel–Crafts green polymerization. Abstract : Efficient emissive fluorene-based p–n conjugated porous materials (CPMs) have been constructed via an effective Friedel–Crafts green polymerization. For metal-free and room-temperature processing, CPMs exhibit high fluorescence quantum efficiency of 32%, allowing the fabrication of near-white polymer light-emitting diodes with CIE of (0.30, 0.38).